La morfologia derivazionale tra analisi tradizionali e prospettive teoriche moderne (ACME, 2020)
After a brief overview of the studies in derivative morphology within the tradition of Indo-European linguistics, we examine the interaction between these studies and the theoretical and interpretative models that have emerged in the field of theoretical and typological linguistics. It is shown that this interaction is fruitful on the one hand because it allows a better interpretation of the data offered by historical languages, and on the other because it increases awareness of the peculiar characteristics of the process of reconstruction of the Indo-European protolanguage.